O lobbying da Federação das Indústrias do Estado do Paraná (Fiep): o caso da legislação do ICMS (2005-2015). São Paulo 2017 - Facci, Nilton (2017)
The main purpose of this research was to understand aspects of political relations between industrial entrepreneurs in Paraná and the decisions of the Executive and Legislative branches of the State of Paraná, with emphasis on changes in the ICMS tax legislation. Previous studies point out that there are no studies of this size that address these political relations in national subunits, being one of the main contributions of this research. The research is based on studies that confirm the growth of the relevance of industrial entrepreneurs as political actors, mainly since the National Constituent Assembly. With the theoretical support of Political Pluralism, Polyarchy and Logic of Collective Action, the research uses, as a guide for the analysis, the draft laws listed in the Legislative Agenda of the Industry of the State of Paraná elaborated by Fiep, between the years 2005 to 2015. In the analysis it also considers other draft laws in the Legislative that are not in this Agenda. Based on the data obtained through questionnaires and interviews, this research presents, as main result, that the industrial entrepreneurs of Paraná can develop several actions so that they are, increasingly, relevant political actors as to the ability to influence, ethically and lawfully, changes in ICMS tax legislation. The research also highlighted that in other areas of activity, Fiep has achieved several successes, when verified its actions in the scope of the Logic of Collective Action and in the provision of non-selective services. Regarding analyzes of interest groups that put pressure on the state, it should be noted that these can not be limited by pragmatic and statistical indicators. They must also be supported by the understanding of the internal and external contexts of these groups, for it is in this systemic amplitude that these groups must be understood and analyzed.